Peningkatan Kapasitas Masyarakat dalam Kesiapsiagaan Bencana Banjir di Kelurahan Rawang, Kecamatan Padang Selatan, Kota Padang - Roni Ekha Putera; Ria Ariany; Kusdarini Kusdarini; Tengku Rika Valentina (Warta Pengabdian Andalas, 2019)
The problem of flooding is serious in the city of Padang. Padang Selatan sub-district is one of the sub-districts that has experienced one of the worst floods in 2018 in Rawang Urban Village each year. Flooding is a disaster that can be prevented and minimized its impact. However, avoiding and overcoming the flood disaster cannot be done by the government alone. The effect of floods on the community not only in the form of loss of property and buildings, also flooding also dramatically affects the community's economy and overall community development, especially health and education. The purpose of this activity is to provide training in increasing the capacity of the population in flood preparedness by using a focused lecture and discussion method by involving all stakeholders (elements of the community) in Rawang Village. The results obtained from this activity are that the community's awareness is still lacking towards flood prevention, This can be seen from the way of life of the population which most of them always do not reflect the culture of clean and healthy living. The community is accustomed to throwing garbage along the river and drainage without caring about the impact. With this activity, it is expected that in the future, the anticipation of flood disasters by increasing community capacity in preparedness. The community was targeted for capacity building because the population was affected by the natural flood.